2019
DOI: 10.1152/ajpheart.00251.2018
|View full text |Cite
|
Sign up to set email alerts
|

Transient outward K+ current can strongly modulate action potential duration and initiate alternans in the human atrium

Abstract: Efforts to identify the mechanisms for the initiation and maintenance of human atrial fibrillation (AF) often focus on changes in specific elements of the atrial “substrate,” i.e., its electrophysiological properties and/or structural components. We used experimentally validated mathematical models of the human atrial myocyte action potential (AP), both at baseline in sinus rhythm (SR) and in the setting of chronic AF, to identify significant contributions of the Ca2+-independent transient outward K+ current (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 137 publications
1
25
0
Order By: Relevance
“…The figure shows that there are marked differences both in the electrical restitution and steady-state frequency dependent curves. The nature and mechanism of the frequency dependent APD changes (Carmeliet, 1977;Elharrar and Surawicz, 1983;Obreztchikova et al, 2006;Qu et al, 2014;Ni et al, 2019) including electrical restitution are not fully resolved yet. A recent study of Schattock et al (2017) suggested that the slope of the restitution curve depends on the APD of the basic heart rate.…”
Section: Resultsmentioning
confidence: 99%
“…The figure shows that there are marked differences both in the electrical restitution and steady-state frequency dependent curves. The nature and mechanism of the frequency dependent APD changes (Carmeliet, 1977;Elharrar and Surawicz, 1983;Obreztchikova et al, 2006;Qu et al, 2014;Ni et al, 2019) including electrical restitution are not fully resolved yet. A recent study of Schattock et al (2017) suggested that the slope of the restitution curve depends on the APD of the basic heart rate.…”
Section: Resultsmentioning
confidence: 99%
“…The first hypothesis suggests that the steep slope of APD restitution is the alternans driver (852), and this mechanism of arrhythmia is replicated by the ten Tusscher-Noble-Noble-Panfilov model of human ventricular myocyte (732,733). As mentioned above, the ion channel background of APD alternans is attributed to the incomplete recovery and/or deactivation of different inward (I Na , I Ca ) or outward (I to , I Kr , I Ks , I Cl ) currents based on the gating behavior of these channels (841,842). In addition, intracellular ion concentration changes for Ca 21 and Na 1 rapidly or slowly would activate electrogenic NCX or Na 1 -K 1 pumps.…”
Section: Repolarization Alternans and Temporal Repolarization Variabilitymentioning
confidence: 86%
“…Local regional differences in the APD restitution curves (839) may also favor arrhythmogenesis (840). The ion channel background of cycle length-dependent APD changes including APD restitution is attributed to the incomplete recovery and/or deactivation of different inward (I Na , I Ca,L ) or outward (I to , I Kr , I Ks , I Cl ) currents based on the gating behavior of these channels (841,842). In addition, intracellular ion concentration changes for Ca 21 and Na 1 rapidly or slowly would activate electrogenic NCX or Na 1 -K 1 pumps.…”
Section: Frequency Dependence and Restitutionmentioning
confidence: 99%
“…I to -mediated spike-and-dome AP morphology is linked to Brugada syndrome (BrS). TWA is widely observed in BrS and alternans occurs at normal heart rates in which the DI is still very long ( Ni et al, 2019 ). A possible mechanism of BrS based on experiments and computer simulations ( Miyoshi et al, 2005 ) indicates that dynamical instabilities that can cause alternans and other complex AP dynamics also promote dynamic substrates at the tissue level that, differently from static heterogeneity, can potentiate phase-2 reentry.…”
Section: Mechanisms Of Cardiac Alternans and Arrhythmogenesismentioning
confidence: 99%